Industrialización del cacao aplicando buenas prácticas de manufactura y normas el sistema de análisis de peligros y puntos críticos de control ( haccp) en la corporación pepa de oro de la ciudad de Vinces - Fernández Ullon, Lucy (2014)
This thesis consists of Industrialization COCOA APPLYING GOOD MANUFACTURING PRACTICES AND POLICIES IN THE CORPORATION PEPA HACCP GOLDEN CITY VINCES, proposes tools to optimize the quality of production management variables formulating quality management and this allowed us to define elements linked by a part to Total Quality, Technical Tools, Quality Education, features and articles and work done in the production area. The main problem in the biological, chemical and / or physical hazards that may occur at each stage and then perform analyze them to identify for the HACCP plan and these are the risks that are necessary to eliminate or reduce to acceptable levels to producing a safe food...